The Influence of an Islamic Work Environment and Work Motivation on the Performance of Islamic Junior High School Teachers in Padang Panjang - Yusrawati Yusrawati; Supriadi Supriadi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study was motivated by the suboptimal performance of Islamic junior high school teachers in Padang Panjang City, particularly regarding the use of learning media, the utilization of technology, and the implementation of teacher-centered learning. This study aims to analyze the relationship between the Islamic work environment and work motivation on the performance of Islamic junior high school teachers in Padang Panjang City. The study employed a quantitative approach using a correlational research design. The study population consisted of 104 teachers, with a sample of 83 teachers selected using proportional random sampling. Data collection was conducted using a questionnaire with a Likert scale and analyzed using partial and multiple correlations via SPSS software. The results indicate that the Islamic work environment has a positive and significant relationship with teacher performance, with a correlation coefficient of 0.646 in the strong category. Work motivation also has a positive and significant relationship with teacher performance, with a correlation coefficient of 0.822 in the very strong category. Simultaneously, the Islamic work environment and work motivation have a significant relationship with teacher performance, with a multiple correlation coefficient (R) of 0.838 and a coefficient of determination (R Square) of 0.702. This study concludes that the Islamic work environment and work motivation contribute 70.2% to the improvement of teacher performance at Islamic junior high schools in Padang Panjang City.